The pathway to develop an industrial standard device model: From device physics to parameter extraction - Lining Zhang; Mansun Chan (2014 IEEE International Conference on Electron Devices and Solid-State Circuits, 2014)
Device Modeling is always a popular research subject as it does not require expensive equipment. Many models, however, were limited to physical equations and stop at the point of publications. On the other hand, a few models survive the rigorous verification and become widely use as industrial standards. The process to convert an academic model to an industrial standard model requires a different kind of skill sets, which are well described but not perceived by most researchers. In this presentation, the process to enhance an academic model into an industrial model is described. A common platform for users to experience the process to develop a practical model will be introduced.